Model Pembelajaran Agama Islam Pada Pendidikan Inklusi Anak Berkebutuhan Khusus (Autis) (International Forum of Researchers and Lecturers, 2024)
This research explains research on Islamic religious learning models for children with special needs (autism) in elementary schools. The aim of this research is to find out what the Islamic religious learning model is for children with special needs (autism). The method used in this research is a qualitative method, namely library research by going through or studying and examining books or journals and written sources related to this problem. The results of this research show that the Islamic religious learning model for ABK uses inclusive or adaptive learning strategies and small group-based learning and individual support to increase participation and understanding of autistic children towards Islamic religious education